Species confusion in the Australian inflorescence-living genus Pseudanaphothrips (Thysanoptera, Thripidae) - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2025)
An attempt is made to resolve the confused identity of species in the Australian endemic genus, Pseudanaphothrips, with an illustrated key provided to the eight species recognised here. One species, P. querci, was based on a single female from Taiwan and is here recorded from Australia for the first time, and P. achaetus is now found widely from New Zealand to Pacific islands and California. A new generic diagnosis is provided, emphasising the close relationship to Frankliniella, and Isochaetothrips pallidus Steele is considered a new synonym of Pseudanaphothrips frankstoni (Steele). Apart from the historical confusion due to type specimens being poorly slide-mounted, and descriptions that were not diagnostic, biological problems limit the reliability of taxonomic conclusions. Adults appear to disperse before reaching mature colouration, often landing on non-host plants, and males are rare in the available samples.